PENGARUH MODAL SENDIRI DAN MODAL PINJAMAN TERHADAP SISA HASIL USAHA PADA KOPERASI DI KOTA PALU - WULANDARI HAIDIR, SRI (Fakultas Ekonomi Universitas Tadulako, 2016)
This study aims to obtain explanative findings of (1) simultaneous influence of own capital, loan capital, and business volume on SHU, (2) partial influence own capital on SHU, and (3) the partial influence of capital loans on SHU in Savings and Loans Cooperatives in Palu City. The subject of this study is the Savings and Loans Cooperatives in Palu, with research objects of own capital, loan capital, and SHU from 2010-2014. The type of data is quantitative. Data collection method is documentary recording and analyzed with multiple linear regressions. The results shows that: (1) simultaneously, there is a positive and significant influence of own capital and borrowed capital on cooperatives? SHU with F-value of 6.421; (2) partially, there is a positive and significant influence of own capital on SHU with t-value of 2.788; and (3) partially, there is a positive and significant influence of loan capital against SHU t-value of 3.349 on savings and loan cooperatives in Palu.